KEANEKARAGAMAN JENIS OPHIUROIDEA (BINTANG MENGULAR) DI PERAIRAN WORI, MINAHASA UTARA, SULAWESI UTARA - Yusron, Eddy (Makara Journal of Science, 2010)
Ophiuroidea Biodiversity in the Wori Waters, Minahasa Utara, North Sulawesi. A total of 10 Ophiuroidea species was found in Wori waters, North Sulawesi. The Ophiuroideas the most were relatively common group in seagrass area. The quantitative on the abundance data revealed the highest diversity index of faunal assemblage at Wori II transect 3 (H = 4.276) while the highest evenness index was exhibited by the Ophiuroidea from Wori III transect 6 (J = 0.821).